TanDEM-X Acquisition Planner - Ortega-Miguez, Carlos; Schulze, Daniel; Polimeni, Maria Donata; Böer, Johannes; Rizzoli, Paola; Bachmann, Markus (2012)
The TanDEM-X mission (TerraSAR-X add-on for Digital Elevation Measurement) consists of two almost iden-tical satellites, TerraSAR-X (TSX) and TanDEM-X (TDX), launched in 2006 and 2010 respectively. They form a single-pass SAR interferometer with adjustable baselines in cross and along-track directions. The primary mis-sion goal is to generate a global digital elevation model (DEM) with an unprecedented relative height accuracy of 2 meters at 12 meters posting. The flexibility of the formation flying system provides a configurable platform that allows carrying out secondary mission goals like local DEMs of even higher accuracy and along-track inter-ferometry applications . The mutual satellite lifetime of three years constraints the time to fullfil the TanDEM-X primary mission goal. To achieve the mission requirements in terms of height resolution, the acquisition strategy has been divided into three phases. During the first and second phases, corresponding to the first and second years, two global Earth acquisitions (except Antarctica) are planned, each with a different height of ambiguity target. The difficult ter-rain will be scheduled to the third year. This paper provides an overview of the TanDEM-X Acquisition Planner (TAP), an IOCS subsystem in charge of deriving the global DEM acquisition timeline for each phase, its corresponding radar parameters at datatake level, and the satellites formation. The global acquisition scenario and the target height of ambiguity are the TAP’s main drivers.